2017
DOI: 10.1186/s12889-017-4084-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the quality of childhood tuberculosis diagnosis in Cambodia: a cross-sectional study

Abstract: BackgroundCambodia is one of the 22 countries with the highest TB burden. While childhood TB is estimated to make up 10–20% of total TB cases in high-burden settings, this proportion ranges from 1.3 to 39.4% throughout Cambodia’s provinces, suggesting potential under- and over-diagnosis of childhood TB, subnationally. The proportion of case notifications classified as extrapulmonary TB out of total TB case notifications in children is 87%, greatly exceeding the expected global range of 20–30%. There is a gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 15 publications
(14 reference statements)
2
28
4
Order By: Relevance
“…One study found socioeconomic status and prior anti-TB treatment were strong determinants of utilisation of bacteriological tests [ 23 ]. Behavioural or health system issues may also play a role where services are available but underutilised- perhaps due to patients’ lack of awareness or perceived poor quality [ 22 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found socioeconomic status and prior anti-TB treatment were strong determinants of utilisation of bacteriological tests [ 23 ]. Behavioural or health system issues may also play a role where services are available but underutilised- perhaps due to patients’ lack of awareness or perceived poor quality [ 22 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…1). Asking about contacts with TB patients should be included as part of the initial history for children in nutrition programs, as outlined in the WHO manual on the management of severe malnutrition, followed by a diagnostic algorithm, like ours [20,21] ( Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…But, studies from Nepal, Uganda and Cambodia found that clinicians werenot preferring clinical judgement for the diagnosis of TB, especially among childhood TB cases. 16,17,18 Hence the focus of NTP should be placed on rational use of GeneXpert machines as well as capacity building of clinicians for clinical diagnosis of TB cases.…”
Section: Decreasing Diagnosis Of Clinically Confirmed Tb Casesmentioning
confidence: 99%